RANCANG BANGUN SISTEM PENYIRAMAN TANAMAN SAYUR BERBASIS ARDUINO DENGAN SENSOR KELEMBABAN TANAH - Sampurna Dadi Riskiono; Roy Harry Syidiq Pamungkas; Yudha Arya (Jurnal Ilmiah Mahasiswa Kendali dan Listrik, 2020)
Development at this time is increasing, people expect a tool or technology that can help human work, so technology becomes a necessity for humans. This final task is made a device that can do the job of watering tomato plants automatically. This tool aims to replace the manual work becomes automatic. The benefit of this tool is that it can facilitate the work of humans in watering chili plants. This tool uses a soil moisture sensor which acts as a soil moisture detector and sends an order to Arduino Uno to turn on the relay driver so that the wiper motor can splash water according to the needs of the soil automatically. The making of this final project is done by designing, making and implementing system components which include Arduino uno as a controller, driver relay to blow on and off the wiper motor, LCD (Linquit Cristal Display) to display the percentage value of water content